Enhanced formation of isoprene‐derived organic aerosol in sulfur‐rich power plant plumes during Southeast Nexus. Issue 18 (29th September 2016) - Xu, Lu; Middlebrook, Ann M.; Liao, Jin; de Gouw, Joost A.; Guo, Hongyu; Weber, Rodney J.; Nenes, Athanasios; Lopez‐Hilfiker, Felipe D.; Lee, Ben H.; Thornton, Joel A.; Brock, Charles A.; Neuman, J. Andrew; et al.
Abstract: We investigate the effects of anthropogenic sulfate on secondary organic aerosol (SOA) formation from biogenic isoprene through airborne measurements in the southeastern United States as part of the Southeast Nexus (SENEX) field campaign. In a flight over Georgia, organic aerosol (OA) is enhanced downwind of the Harllee Branch power plant but not the Scherer power plant. We find that the OA enhancement is likely caused by the rapid reactive uptake of isoprene epoxydiols (IEPOX) in the sulfate‐rich plume of Harllee Branch, which was emitting at least 3 times more sulfur dioxide (SO2 ) than Scherer, and more aerosol sulfate was produced downwind. The contrast in the evolution of isoprene‐derived OA concentration between two power plants with different SO2 emissions provides an opportunity to investigate the magnitude and mechanisms of particle sulfate on isoprene‐derived OA formation. We estimate that 1 µg sm −3 reduction of sulfate would decrease the isoprene‐derived OA by 0.23 ± 0.08 µg sm −3 . Based on a parameterization of the IEPOX heterogeneous reactions, we find that the effects of sulfate on isoprene‐derived OA formation in the power plant plume arises from enhanced particle surface area and particle acidity, which increases both IEPOX uptake to particles and subsequent aqueous‐phase reactions, respectively. The observed relationships between isoprene‐OA, sulfate, particle pH, and particle water in previous field studies are explained using these findings. Key Points: Isoprene‐OA formation is rapid via the IEPOX reactive uptake downwind of power plant plumes Sulfate enhances isoprene‐OA formation due to both enhanced particle surface area and particle acidity About 25% of the OA reduction in the southeastern United States could arise from the sulfate control over isoprene‐OA formation